The multiplicity and the frequent changes of the tax legislation in the Greek Tax Administration - Komninos Dimitrios; Dermatis Zacharias; Anastasiou Athanasios; Liargovas Panagiotis (Technium Social Sciences Journal, 2020)
The most important factor contributing to the slowdown in the development of entrepreneurship in Greece is related to frequent changes in tax legislation and to the ambiguity and regression in the tax authorities’ decisions and clarifications. As the complexity of tax legislation increases, its impact on citizens and businesses becomes increasingly burdensome and the risk to businesses continues to increase. Tax legislation is useful not to leave room for controversy and different interpretations, in order not to require the issuance of numerous circulars, with clarifications to understand this law. Tax legislation must be simple to understand by taxpayers without the need for multiple procedures. Frequent changes and the complexity of tax legislation act as barriers to the arrival of new businesses or the growth of those operating. Greece needs simplified and codified tax legislation. The quality and quantity of tax legislation significantly affects both the operation of the Tax Administration and the daily life of taxpayers. The purpose of this paper is to present the pace at which tax laws are modified and replaced by new ones, creating insurmountable difficulties in the development of entrepreneurship in Greece, as well as the necessity to create a stable tax environment.